PENGARUH LEVERAGE KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR FOOD AND BEVERAGE DI BURSA EFEK INDONESIA - Fithriah Napu (Mega Aktiva, 2019)
The purpose of this study is to examine and analyze the effect of financial leverage consisting of LDE (Long Term Debt To Equity Ratio), DE (Debt To Equity Ratio), DSR (Debt-Size Ratio), DM (Debt Maturity Ratio) Against Manufacturing Company Value On the Indonesian Stock Exchange. The sample used in this study 51 came from the financial statements of 17 manufacturing companies listed on the Indonesia Stock Exchange from 2005 to 2007 and met established criteria, with each company totaling 3 financial statements (three years). The analysis technique used is multiple regression analysis, with the help of SPSS version 16 software. The results of the study suggest that (1) Financial leverage consisting of LDE (Long term debt to equity ratio), DE (Debt to equity ratio), DSR (Debt-size ratio), DM (Debt maturity ratio) simultaneously affect Company Value Manufacturing on the Indonesia Stock Exchange (IDX). (2). Partially the influence of financial leverage variables that significantly influence the value of the company in this study are DSR (Debt-size ratio) and DM (Debt maturity ratio), while LDE (Long term debt to equity ratio), DE (Debt to equity ratio do not have significant influence on Company Value (3) The coefficient of determination (R2) of 0.365 indicates that the accuracy of the model for the sake of prediction is enough to consider factors Financial leverage can contribute an influence of 36.5% on Company Value.